Dietary Components and Immune Function (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Each stage of the body's immune response relies on the presence of nutrients. The energy and nutrient needs of the immune system can be met from exogenous diets. Dietary components can influence the development and maintenance of the immune system or play a very specific role in reducing chronic inflammation. The healthy diet regulates the fine balance of pro-inflammatory and anti-inflammatory mediators and immune cells to help the immune system fight infection. They can also protect our bodies from harmful autoimmune diseases, chronic inflammatory diseases or cancer, and fetal infection following cancer or before harmful autoimmune diseases. In contrast, malnutrition or excessive intake of micronutrients can impair immune function. For example, iron supplementation will increase morbidity and mortality in those in malaria-endemic regions. Researchers have always had many questions about nutrition and the immune system: How can different dietary components effectively treat immune deficiencies associated with inadequate intake? Can specific nutritional interventions further enhance immune function in subclinical settings to prevent inflammatory disease infection or chronic disease? The authors of papers included in this Special Issue shared some valuable knowledge, including but not limited to research on different dietary components related to the immune system. Ultimately, we hope that this reprint will be useful for clinical practitioners and inspire further innovative research.